Clinical teaching in paediatrics: understanding perceptions, motives and concerns. Issue 5 (5th December 2008) - Klaber, R E; Pollock, I
Abstract : Background: Children and young people are used as cases and standardised patients in clinical exams and teaching courses. Consultation with them suggests that education and training are areas they feel they should actively participate in. Aims: To examine the perceptions, motives and concerns of children and young people participating in exam-focused clinical teaching, and to compare these views with those of their parents, trainees and tutors. Methods: Consultation and a pilot study were used to design an anonymised questionnaire with 5-point Likert scales and free text answers. This was sent to 112 children and young people, their parents, and tutors and trainees attending a clinical teaching course. Results were analysed using the Mann–Whitney U test. Results: 71% of the questionnaires sent to children and young people and their parents were completed. For children and young people the major reasons for taking part were the enjoyment of helping people to learn (92% agreement) and wanting to "give something back" (85% agreement). Parents put significantly more emphasis on giving something back than anything else. Tutors and trainees felt the chance for children and young people to earn pocket money was their most important motivation. The major problem highlighted was that it is tiring being repeatedly examined. All children and young people and their parents said that they would participate in future clinical teaching. Conclusions: This study demonstrates that in the context of well-planned, structured clinical teaching, most children and young people are primarily motivated to participate to help educate doctors.